Amiodarone: A Newly Discovered Association with Bilateral Vestibulopathy - Gürkov, Robert (Frontiers in Neurology, 2018)
Background: Bilateral vestibulopathy is a debilitating disorder characterized by the hypofunction of both vestibular end organs or nerves. The most frequent identifiable causes of bilateral vestibulopathy are ototoxic drug effects, infectious and autoimmune disorders. However, tThe majority of cases, however, remain idiopathic. Very recently, the first discovery of a clinical case of Amiodarone-associated bilateral vestibulopathy was has been reported. Methods: An overview of the literature concerning the relation between amiodarone toxicity and bilateral vestibulopathy is presented and discussed. Results: Older reports on amiodarone-induced symptoms of vertigo and gait instability lack a description of vestibular function test results. Recent evidence from retrospective studies including vestibular function testing in patients taking amiodarone have identified the drug as the hitherto unsuspected unsuspected potential cause of a relatively large proportion of cases with “idiopathic” bilateral vestibulopathy. Conclusion: Patients who receive amiodarone should be monitored with vestibular function testing in order to recognize potential adverse effects on the vestibular system and allow for an informed decision on possible drug reduction or withdrawal.